1985
DOI: 10.1029/jd090id01p02425
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically produced ozone in the emission from large‐scale tropical vegetation fires

Abstract: An aircraft measurement program was undertaken in the savanna regions of central South America in the dry season of 1980 to investigate the atmospheric effects of large-scale biomass burning. The smoke from the fires was found to be largely confined within an approximately 3-km-deep boundary layer capped by a subsidence inversion or a stable layer. This condition typically persists for week-long periods as a result of the synoptic subsidence occurring during the dry season. Photochemical production of ozone oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(53 citation statements)
references
References 15 publications
2
50
0
1
Order By: Relevance
“…According to Piazena (1996), UV-A irradiation at 10 km height can be 70-150 % higher than at ground level depending on solar elevation. Coupled with the high levels of O 3 found in aged BB plumes (Delany et al, 1985;Andreae et al, 1988;Crutzen and Andreae, 1990;Ziemke et al, 2009; Konovalov et al, 2011;Dupont et al, 2012;Martins et al, 2012;Akagi et al, 2013), uptake of O 3 by BBA compounds can be significant. For example, using a solar elevation angle of ∼ 70 • C, which roughly corresponds to a summer afternoon in the midwestern US, UV-A irradiation at 10 km height is 9.52 × 10 15 photons cm −2 s −1 .…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Piazena (1996), UV-A irradiation at 10 km height can be 70-150 % higher than at ground level depending on solar elevation. Coupled with the high levels of O 3 found in aged BB plumes (Delany et al, 1985;Andreae et al, 1988;Crutzen and Andreae, 1990;Ziemke et al, 2009; Konovalov et al, 2011;Dupont et al, 2012;Martins et al, 2012;Akagi et al, 2013), uptake of O 3 by BBA compounds can be significant. For example, using a solar elevation angle of ∼ 70 • C, which roughly corresponds to a summer afternoon in the midwestern US, UV-A irradiation at 10 km height is 9.52 × 10 15 photons cm −2 s −1 .…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…In the atmosphere, however, BBA particles are exposed to gas phase oxidants such as O 3 , resulting in multiphase chemical reactions, which can cause chemical and physical modification of the particles, a process known as chemical ageing (Hennigan et al, 2010;Kessler et al, 2010;Hennigan et al, 2011;Knopf et al, 2006Knopf et al, , 2011Shiraiwa et al, 2012). It has been shown that O 3 can be photochemically created in BB plumes, with reported concentration levels as high as 100 ppb (Delany et al, 1985;Andreae et al, 1988;Crutzen and Andreae, 1990;Ziemke et al, 2009;Konovalov et al, 2011;Dupont et al, 2012;Martins et al, 2012;Akagi et al, 2013). Therefore, heterogeneous oxidation reactions inside a BB plume can cause chemical modification of particles and biomolecular marker species, potentially having subsequent effects on source apportionment (Robinson et al, 2006b;Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, areas with the highest convective cloud activity showed the highest production of these species. As it is typical for high ozone concentrations to form in evolving smoke plumes (Delany et al, 1985;Hobbs et al, 1996), there can be adequate oxidation potential in the environment for secondary processes to occur.…”
Section: Particle Evolution Processesmentioning
confidence: 99%
“…Numerous investigations of the atmospheric impact of tropical fires have given clear evidence that elevated levels of ozone over South America and Africa are due to the excessive burning of forests and savannah, the rain forest otherwise acting as an important net sink for ozone (e.g., Delany et al, 1985;Browell et al, 1988;Gregory et al, 1988;Crutzen and Andreae, 1990;Richardson et al, 1991;Kirchhoff and Marinho, 1994;Kirchhoff, 1996;Kirchhoff et al, 1996). A retrieval of satellite measurements has given evidence of substantial ozone export to the tropical oceanic regions (Fishman et al, 1986;Fishman and Larsen, 1987), a strong burden to the otherwise clean troposphere in the Southern Hemisphere during certain periods of the year.…”
Section: Introductionmentioning
confidence: 99%